Light curve analysis of some eclipsing binary systems - Alenazi, M. S.; Elkateeb, M. M. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We present the first photometric observations and light curve modelling of the discovered systems GSC 01870-00458 and USNO-A2.0-0975 04721840. Our modelling was carried out using a recent Windows interface version of Wilson and Devinney code based on model atmospheres provided by Kurucz. The accepted models revealed absolute and physical parameters that can be used to study the evolutionary states of systems. Представлены первые фотометрические наблюдения и моделирование кривых блеска обнаруженных систем GSC 01870-00458 и USNO-A2.0-0975 04721840. Моделирование проводилось с использованием последней версии кода Уилсона и Девинни для интерфейса Windows на основе моделей атмосфер Куруца. Принятые модели позволили определить физические параметры, которые могут быть использованы для изучения эволюционных состояний систем, а также спектральные классы компонентов системы.
Keywords: Astrophysics